ROS signaling under metabolic stress: cross-talk between AMPK and AKT pathway - Yang Zhao (Molecular Cancer, 2017)
Abstract Cancer cells are frequently confronted with metabolic stress in tumor microenvironments due to their rapid growth and limited nutrient supply. Metabolic stress induces cell death through ROS-induced apoptosis. However, cancer cells can adapt to it by altering the metabolic pathways. AMPK and AKT are two primary effectors in response to metabolic stress: AMPK acts as an energy-sensing factor which rewires metabolism and maintains redox balance. AKT broadly promotes energy production in the nutrient abundance milieu, but the role of AKT under metabolic stress is in dispute. Recent studies show that AMPK and AKT display antagonistic roles under metabolic stress. Metabolic stress-induced ROS signaling lies in the hub between metabolic reprogramming and redox homeostasis. Here, we highlight the cross-talk between AMPK and AKT and their regulation on ROS production and elimination, which summarizes the mechanism of cancer cell adaptability under ROS stress and suggests potential options for cancer therapeutics.